2016
DOI: 10.4271/2016-32-0051
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Behavior of Three-Wheel Vehicles When They Pass Over a Low μ Road Surface

Abstract: In recent years three-wheel camber vehicles, with two wheels in the front and a single rear wheel, have been growing in popularity. We call this kind of vehicle A "Leaning Multi Wheel category Vehicle" (hereinafter referred to as a "LMWV"). A LMWV has various characteristics, but one of them stands out in particular. When a LMWV is cornering, if one of the front wheels passes over a section of road surface with a low friction coefficient, there is very little disturbance to the vehicle's behavior and can conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Other researchers are focused on the effects of passing over low friction coefficient surfaces, where the riders of three-wheel vehicles have indicated that one noteworthy characteristic is the vehicle's stability when cornering, over a low friction surface, like slippery or wet road. As indicated, under these conditions the decrease in lateral force on one front tire, passing over the low friction road surface, is compensated by the other front tire [9].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Other researchers are focused on the effects of passing over low friction coefficient surfaces, where the riders of three-wheel vehicles have indicated that one noteworthy characteristic is the vehicle's stability when cornering, over a low friction surface, like slippery or wet road. As indicated, under these conditions the decrease in lateral force on one front tire, passing over the low friction road surface, is compensated by the other front tire [9].…”
Section: Introductionmentioning
confidence: 75%
“…In general, tire friction data are linked to road conditions (dry, wet, ice), as also on different road material types (such as asphalt, gravel etc.) [7,9,27]. Nevertheless, motorcycle tires are different than car tires and have different shapes of contact patch on the road [27,28].…”
Section: Braking Forces and Tire Frictionmentioning
confidence: 99%
“…Such data are mainly related to road conditions (dry, wet, or ice), as also on different road material types (such as asphalt, gravel, etc.) [40][41][42]. Experimental and theoretical results for car tires in contact with a road made from tarmac in dry conditions can be found in [42,43], presenting a range of values 0.7 < µ < 1.0.…”
Section: Tire Modelingmentioning
confidence: 98%